FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN LOW BACK PAIN PADA PEKERJA PENGRAJIN BATU BATA - Junita Fabanjo, Ivonne; Hendrik, Hendrik; Arpandjaman, Arpandjaman; Fredy Saputra, M. Khalid; Auliah, Rezki (Ensiklopedia of Journal, 2024)
Low Back Pain (LBP) is pain felt in the lower back whose source is the spine of the spinal region or lower back, muscles, nerves, or other regional structures in the area. The results of a preliminary study conducted on 10 brick craftsmen workers using a questionnaire, it is known that 8 out of 10 with a presentation of 80% of workers have complaints of low back pain, from observations made, that many awkward postures in the work performed by workers can be seen. The purpose of the study was to determine the factors associated with low back pain complaints in brick craftsmen workers. This research is an observational analytical research with the approach The type of research conducted in this study is quantitative research with a cross sectional study design. The research was conducted in Jantera Village, precisely in Java Hamlet, Pasar 2 Dondong, Pasar 2 east, Pasar 2 west and Pasar 3 Wampu District in 2022. The sample in the study was workers who worked on brick making which amounted to 76 people. Sampling technique by means of cluster random sampling. Data collection tools using a research questionnaire. Data analysis was carried out univariate and bivariate using the SPSS program. The results showed that there was a relationship between working time (p value 0.042), Manual Material Handling (p value 0.002) and workload (p value 0.000) with Low complaints.Keywords: Workload, Low Back Pain, Craftsmen